2012
DOI: 10.3233/wor-2012-0295-1149
|View full text |Cite
|
Sign up to set email alerts
|

Using environmental affordances to direct people natural movement indoors

Abstract: Understanding and predicting people's displacement movement is particularly important for professionals involved in planning complex buildings (e.g., hospitals, convention centers, subway stations and university campus). Some decisions taken by the visitors while choosing what route to follow can be influenced by some environmental cues which can act as a factor of attraction, influencing the wayfinding process. Therefore, the main objective of this study was to evaluate the hypotheses that, in the context of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 5 publications
0
22
0
Order By: Relevance
“…In a series of experiments, Van Tilburg and Igou (2014) examined which of four heuristics—the action-continuation heuristic, the initial segment heuristic, the least-angle heuristic, and the hill-climbing heuristic—individuals preferred while navigating a maze with equally functional routes at a choice point and found that participants behaved in a way consistent with use of the action-continuation heuristic. In three other studies, navigation patterns of people were investigated in two types of intersections: T-type intersections (nodes with two alternatives of turning left or right) and F-type intersections (nodes with two alternatives of continuing straight or turning right/left) ( Vilar et al, 2012 , 2014b , 2015 ). Findings showed that the type of intersection affected people’s behavior, such that brighter corridors were preferred at both T-type and F-type intersections and wider corridors at only T-type intersections.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a series of experiments, Van Tilburg and Igou (2014) examined which of four heuristics—the action-continuation heuristic, the initial segment heuristic, the least-angle heuristic, and the hill-climbing heuristic—individuals preferred while navigating a maze with equally functional routes at a choice point and found that participants behaved in a way consistent with use of the action-continuation heuristic. In three other studies, navigation patterns of people were investigated in two types of intersections: T-type intersections (nodes with two alternatives of turning left or right) and F-type intersections (nodes with two alternatives of continuing straight or turning right/left) ( Vilar et al, 2012 , 2014b , 2015 ). Findings showed that the type of intersection affected people’s behavior, such that brighter corridors were preferred at both T-type and F-type intersections and wider corridors at only T-type intersections.…”
Section: Resultsmentioning
confidence: 99%
“…Floor plan configuration -navigation pattern 6 Peponis et al, 1990;Haq, 2003;Haq and Zimring, 2003;Hölscher et al, 2006Hölscher et al, , 2012Lu and Ye, 2019 The relationship between regions-and spatial memories Regions-spatial memories 2 Wang and Brockmole, 2003;Montello and Pick, 1993 The relationship between regions-and spatial updating Regions-spatial updating 1 Mou and Wang, 2015 The relationship between edges -and spatial memories. Edges -spatial memories 1 Buckley et al, 2016 The relationship between paths -and navigation pattern Paths -navigation pattern 6 Butler et al, 1993;Frankenstein et al, 2012;Hidayetoglu et al, 2012;Wiener et al, 2012;Vilar et al, 2014bVilar et al, , 2015 The relationship between paths -and psychological state Paths -psychological state 2 Vilar et al, 2013Vilar et al, , 2014b The relationship between nodes -and navigation pattern Nodes -navigation pattern 4 Vilar et al, 2012Vilar et al, , 2014bVilar et al, , 2015Van Tilburg and Igou, 2014 The relationship between nodes -and psychological state Nodes -psychological state 3 Tang et al, 2009;Vilar et al, 2013Vilar et al, , 2014b The relationship between landmarks -and spatial memories Landmarks -spatial memories 6 Jansen-Osmann and Wiedenbauer, 2004;Jansen-Osmann and Fuchs, 2006;Davis et al, 2008;Hidayetoglu et al, 2012;Werkhoven et al, 2014;Sameer and Bhushan, 2015 The relationship between landmarks -and spatial updating Landmarks -spatial updating 1 Wan et al, 2012 The relationship between landmarks -and logical associations.…”
Section: The Relationship Between Spatial Memories and Agementioning
confidence: 99%
“…Moreover, only the brighter corridor was rated higher for comfort, suggesting that illumination is a contributing factor. Also, Vilar et al [115] concluded that wider and more illuminated routes were preferred.…”
Section: Videosmentioning
confidence: 99%
“…Other architectural features that have been found to influence path choice behaviour include the width and ceiling height of the path [54,53,52]. Salient and attention-grabbing objects offering qualities of beauty, curiosity, or educational value in an area have also been found to impact spatial behaviour in public spaces [38].…”
Section: Understanding Spatial Behaviour In Public Spacesmentioning
confidence: 99%